Skin Lesions Associated with Nutritional Management of Maple Syrup Urine Disease - Jaraspong Uaariyapanichkul; Puthita Saengpanit; Ponghatai Damrongphol; Kanya Suphapeetiporn; Sirinuch Chomtho (Case Reports in Dermatological Medicine)
Introduction. Maple syrup urine disease (MSUD) is an inborn error of branched chain amino acids (BCAAs) metabolism. We report an infant with MSUD who developed 2 episodes of cutaneous lesions as a result of isoleucine deficiency and zinc deficiency, respectively. Case Presentation. A 12-day-old male infant was presented with poor milk intake and lethargy. The diagnosis of MSUD was made based on clinical and biochemical data. Management and Outcome. Specific dietary restriction of BCAAs was given. Subsequently, natural protein was stopped as the patient developed hospital-acquired infections which resulted in an elevation of BCAAs. Acrodermatitis dysmetabolica developed and was confirmed to be from isoleucine deficiency. At the age of 6 months, the patient developed severe lethargy and was on natural protein exclusion for an extended period. Despite enteral supplementation of zinc sulfate, cutaneous manifestations due to zinc deficiency occurred. Discussion. Skin lesions in MSUD patients could arise from multiple causes. Nutritional deficiency including isoleucine and zinc deficiencies can occur and could complicate the treatment course as a result of malabsorption, even while on enteral supplementation. Parenteral nutrition should be considered and initiated accordingly. Clinical status, as well as BCAA levels, should be closely monitored in MSUD patients.